Crashworthiness analysis of double section bi-tubular thin-walled structures. (March 2017) - Vinayagar, K.; Senthil Kumar, A.
Abstract: This article aims to present the crashworthiness performance of double section bi-tubular thin-walled structures. Double section bi-tubes were made from stainless steel sheet and consist of an outer circular cylinder and an inner tube with any one of polygonal section such as triangle, square or hexagon. By keeping the outer cylinder dimensions constant, the effect of changes in the inscribed diameter of polygonal section and the various polygonal section of the inner tube on quasi-static axial compression is studied. Bi-tubular structures with hexagonal inner tube have more energy absorption capability than the other bi-tube combinations and the single cylinder. Highlights: Crashworthiness performance of double section bi-tubular structures was investigated. Energy absorption increased with inscribed diameter of polygonal section. Influences of polygonal section of the inner tube on crashworthiness also studied. Bi-tubes with hexagonal inner tube combination had more energy absorption capability.